The panic of 1893 : the untold story of Washington State's first depression - Ramsey, Bruce A. (Caxton Press, 2018)
In 1893 Washington, a new state with new people, plunged into the last depression of the 19th century. Banks failed. Railroad building stopped. Money became so scarce that Port Angeles and Bellingham made their own. Jobless men sawed wood, picked blackberries, and dug clams. In Spokane, the town's richest man was wiped out, and from Tacoma and Seattle protesters set off for Washington, D.C., on foot and by stealing rides on trains. In The Panic of 1893, former Seattle newspaper columnist Bruce A. Ramsey tells the story of how people survived and how their resilience defined their new state."--